2011
DOI: 10.1002/mnfr.201100216
|View full text |Cite
|
Sign up to set email alerts
|

Compound CVT‐E002 attenuates allergen‐induced airway inflammation and airway hyperresponsiveness, in vivo

Abstract: Immune modulation has been a sought after means of therapy for atopic diseases. CVT-E002 is an extract derived from North American Ginseng shown to promote T-helper-1-like responses. We determined what effect CVT-E002 could have in a mouse model of atopic asthma. We report that oral CVT-E002 inhibited the development of allergic airway inflammation and airway hyperresponsiveness. This correlated with an increased presence of interferon-γ in the lung, and also increased regulatory T cells and IL-10. The ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
(18 reference statements)
1
6
0
Order By: Relevance
“…AGRPS and AQ extracts are not antagonists of LPS because they have low stimulatory effect and also requires pretreatment before they can suppress LPS stimulation. The data from this study supports the reported CVT-E002 TM immunostimulatory [22,29,48,[59][60][61][62] and suppression of proinflammatory effects [21,63] under basal and induced proinflammatory conditions respectively. Therapies directed at the neutralization of proinflammatory mediators Fig.…”
Section: Discussionsupporting
confidence: 93%
“…AGRPS and AQ extracts are not antagonists of LPS because they have low stimulatory effect and also requires pretreatment before they can suppress LPS stimulation. The data from this study supports the reported CVT-E002 TM immunostimulatory [22,29,48,[59][60][61][62] and suppression of proinflammatory effects [21,63] under basal and induced proinflammatory conditions respectively. Therapies directed at the neutralization of proinflammatory mediators Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to most of other American ginseng products, the extract contains no ginsenosides. This product has been intensively studied recently as immunomodulator [9, 17]. The powder content of COLD-fX capsule was dissolved in phosphate-buffered saline (PBS, pH 7.4), filtered through 0.45  μ m Millipore membranes to remove particulate material and any bacterial contaminants, and used fresh the same day.…”
Section: Methodsmentioning
confidence: 99%
“…RG-II isolated from Panax ginseng induced the Th1/Th2 immune response and IFNγ expression in mice with ovalbumin-induced asthma, while IL-4 and GATA3 expression and eosinophil populations were decreased in the bronchoalveolar lavage fluid [92]. CVT-E002 derived from North American Ginseng also activated Th1 responses and increased IL-10 expression, resulting in the attenuation of allergic airway inflammation and airway hyperresponsiveness [93]. These suggest that ginseng polysaccharides can stimulate the Th1 cell immune responses, resulting in the attenuation of asthma with the suppression of Th2 cell activation.…”
Section: Anti-allergic Effects Of Ginseng Constituentsmentioning
confidence: 97%
“…Therefore, they are metabolized by gut microbiota in the intestine, which transform hydrophilic ginsenosides such as ginsenosides Rb1, Rb2, and Re into hydrophobic ginsenosides such as CK and Rh1 [13,20,97,98]. Comparing the anti-allergic activities of naïve ginsenosides Rb1, Rg3, and Re to those of their metabolite ginsenosides CK, Rh2, and Rh1, metabolites (ginsenosides CK, Rh2, and Rh1) suppress allergic reactions such as passive cutaneous anaphylaxis, scratching, and asthma more potently than parental ginsenosides Rb1, Rg3, and Re, respectively [38,62,81,82,93]. However, oral gavage of antibacterials suppresses their biotransformations and attenuates anti-allergic activities in mice.…”
Section: Gut Microbiota Enforce Anti-allergic Activities Of Ginseng Cmentioning
confidence: 99%